Observações sôbre a quantidade de milho amarelo necessária para prevenir a avita-minose a em pintos - Graner, E. A.; Bergamin, A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1949)
The authors tried to check in this experiment the minimum of yellow corn necessary for preventing avitaminosis A in chickens. It was observed, in balanced ration with 50% of corn, that: a) 20% of dent and yellow grains and 30% of flint and white grains were insuficient to prevent avitaminosis A. b) 20% of flint and orange grains and 30% of flint and white grains or 40% of either colored grains and 10% of flint, and white grains did not show evident signs of avitaminosis A during the 12 weeks of the experiment. The ration containing 20% of flint and orange grains is pratically equivalent to the ration containing 40% of dent and yellow grains, regarding the content of pro-vitamina A. However, it was not possible to conclude if these dosage are sufficient to give the necessary vitamina A for normal development of the chickens since the table 3 seems to indicate a negative correlation between the amount of pigment in the ration and the mortality of the animals.